A NEW ERA OF ONLINE DATING? AN ANALYSIS OF THE APPLICATION OF ARTIFICIAL INTELLIGENCE IN DATING APPS - Rodrigues, Luciana Ribeiro (AoIR Selected Papers of Internet Research, 2026)
The phenomenon of online dating has undergone significant transformations over the past five years, ranging from the record surge in users during the Covid-19 pandemic to the so-called "dating app winter," marked by consecutive declines in active users since 2023. This paper aims to analyze how the incorporation of artificial intelligence (AI)-based features has been framed as a strategy to counteract this crisis and to what extent these innovations can— or fail to— address users' current dissatisfaction.To this end, we examine news reports on AI implementation in dating apps between 2020 and 2025, identifying how the discourse surrounding this technology has intensified as user dissatisfaction has increased, as evidenced even in reports issued by the companies operating these platforms. We seek to answer the following question: "What are the trends in AI integration in dating apps?" Our hypothesis is that companies are investing in strategies designed to further reduce decision-making time, prioritizing mechanisms that enhance interaction efficiency, minimize discomfort, and ensure greater user satisfaction.This discussion will be framed within critical platform studies and the datafication of life, as well as debates on the commodification of affect and the solutionist approach to the design and modification of these technologies.